Proyek Penguatan Profil Pelajar Pancasila Melalui Kegiatan Cooking di SMP Negeri 1 Medan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) through Fun Cooking activities at SMP Negeri 1 Medan. This activity is part of the implementation of the Independent Curriculum with the theme